KOMPENSATOR HARMONISA PASSIVE FILTER PADA VSD MOTOR INDUKSI BERBASIS MATLAB SIMULINK - Indiarto, Fahmi Bayu (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH; Vol 1 No 01 (2021): September 2021, 2021)
The Sugar Factory Pesantren Baru uses a variable speed drive to regulate the speed of the damper motor on the takuma boiler. VSD (variable speed drive) is an electrical equipment in the form of a rectifier and inverter circuit that uses power electronic components including non-linear loads that contribute harmonics. This research intends to compensator the harmonics by installing a passive filter, if there are harmonics that exceed the specified limits, they will be compensated. The compensator effort is to simulate using matlab simulink. Passive Filter is a solution to reduce harmonics caused by Variable Speed ​​Drive (VSD). This filter is widely chosen because it is economically cheaper than other filters. Passive filter installation can also improve the power factor because passive filters also produce reactive power compensation but according to the large Volt-Ampere limit on the capacitor bank